SISTEM MANAJEMEN KEANGGOTAAN DAN KEGIATAN BERBASIS DIGITAL UNTUK KOMUNITAS KWS YANG LEBIH TERORGANISIR - Ilyas Saputra; Abdus Salam; Niko Kristiawan; Wasis Haryono (CV. Denasya Smart Publisher, 2025)
The KWS Community (Kumpulan Wong Sragen) serves as a collaborative platform for Sragen residents but faces challenges including manual data management, decentralized coordination, and limited transparency. This research aims to design an integrated web-based system to streamline administrative processes, member registration, activity scheduling, and participation tracking. The development employs the Waterfall method—a Software Development Life Cycle (SDLC) approach characterized by sequential phase completion, ensuring structured progression from one stage to the next. Results demonstrate a 60% reduction in administrative workload, improved data accuracy, and real-time communication via a centralized dashboard. Long-term impacts include enhanced member engagement and scalability for similar community models. This study highlights digital transformation's potential in strengthening community-based organizations.